2016
DOI: 10.1111/geer.12073
|View full text |Cite
|
Sign up to set email alerts
|

Regional Inequality and Internal Conflict

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…Finally, de Groeve et al (2014) have highlighted several critical issues with regard to using counted conflicts, supporting our application of the internal conflict risk scores of the ICRG. Lessmann (2016) shows that the ICRG conflict scores and binary conflict variables are correlated and both point in the same direction.…”
Section: Dependent Variable: Political Stability (Stab_icrg)mentioning
confidence: 83%
See 1 more Smart Citation
“…Finally, de Groeve et al (2014) have highlighted several critical issues with regard to using counted conflicts, supporting our application of the internal conflict risk scores of the ICRG. Lessmann (2016) shows that the ICRG conflict scores and binary conflict variables are correlated and both point in the same direction.…”
Section: Dependent Variable: Political Stability (Stab_icrg)mentioning
confidence: 83%
“…The fundamental difference between a terrorist campaign and a civil war is that the former does not hold and manage territory within a nation state. 6 The ICRG internal conflict index is also used in a large number of studies on political stability (e.g., Gupta et al, 2004;Jinjarak, 2009;Bjorvatn and Farzanegan, 2013, 2015, Long, 2008Neumayer, 2004;Lessmann, 2016). We have also examined our hypothesis by using an objective measure of conflict, namely, the maxintyearv413 variable in the UCDP Monadic Conflict Onset and Incidence Dataset (Themnér andWallensteen, 2014 andGleditsch et al, 2002).…”
Section: Dependent Variable: Political Stability (Stab_icrg)mentioning
confidence: 99%
“…The literature has shown that low growth rates are significantly related to a higher risk of conflict [see, e.g., Collier and Hoeffler (2004) or Collier et al (2009)]. The effect is even stronger if the resource curse results in more unequal economic development within a country, which will further increase the risk of conflict [Østby et al (2009[Østby et al ( ), Buhaug et al (2012, and Lessmann (2013)]. All these arguments are evidence for the hypothesis that natural resources increase the risk of internal conflict.…”
Section: Natural Resources and Internal Conflictmentioning
confidence: 99%
“…the regional or spatial inequality between groups of individuals living in different regions. This particular type of inequality has been attracting increasing interest from academics, given that inequality between groups may cause serious problems in a societyfrom inefficient redistribution politics to separatist movements and internal conflict (Østby (2008), Lessmann (2016)). These threats are, of course, more pronounced in ethnically heterogeneous countries due to the coincidence of ethnic inequality and spatial inequality (Kanbur and Venables (2005), Alesina et al (2016)).…”
Section: Introductionmentioning
confidence: 99%